Efecto del Clorpirifos 0,0-dietil 0-(3, 5, 6-tricloro-2-piridil fosforotioato) en machos juveniles de tilapia (Oreochromis spp) (2012)
ABSTRACT: Chlorpyrifos is a highly toxic insecticide to freshwater organisms and little is known regarding its potential to affect endocrine systems at sublethal concentrations. The induction of vitellogenin (Vtg) is a fairly sensitive marker of the effects of estrogenic compounds in juvenile fish. Objective: to evaluate histological changes and Vtg production in juvenile male tilapia (Oreochromis spp) exposed to sublethal concentrations of the insecticide Lorsban® EC (active ingredient chlorpyriphos). Methods: juvenile tilapia were exposed to 4, 8, and 12 µg/L of chlorpyrifos for 28 days in a semistatic system, with tanks receiving a 50% (v/v) daily water change to maintain nominal concentrations of the insecticide throughout the experiment. Subgroups of 3 animals from each concentration batch were euthanized on days 7, 14, 21 and 28 days, and samples of liver, gonads, gills, kidney and brain tissues were taken for routine histopathology examination. Liver and gonads were also processed by immunohistochemistry using monoclonal anti-killifish vitellogenin Vtg ND - 5F8 to detect Vtg. Results: we found significant statistical difference (p < 0.05) for some injuries to the brain (degeneration and gliosis of the optic tectum), kidneys (vacuolar nephrosis and tubular hyaline granules), and liver (karyomegaly, binucleation, and hyaline granules in hepatocytes). Similarly we verified the induction of vitellogenin synthesis in liver and gonads, finding significant difference (p < 0.05) in the expression of this protein between the control group and 4 mg / L with respect to treatment of 8 and 12 mg / L. Conclusion: the results obtained on the induction of vitellogenin in males suggest a general effect of blocking concentrations of Chlorpyrifos for the possible induction of this protein. The mechanisms are not known at this time.